Government versus markets : the changing economic role of the state - Tanzi, Vito (Cambridge : Cambridge University Press, 2011)
Vito Tanzi offers a truly comprehensive treatment of the economic role of the state in the twentieth and twenty-first centuries from a historical and world perspective. The book addresses the fundamental question of what governments should do, or have attempted to do, in economic activities in past and recent periods. It also speculates on what they are likely or may be forced to do in future years. The investigation assembles a large set of statistical information that should prove useful to policy-makers and scholars in the perennial discussion of government's optimal economic roles. It will become an essential reference work on the analytical borders between the market and the state, and on what a reasonable 'exit strategy' from the current fiscal crises should be.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Trade regulation; Economic policy